High-toughness wrapping film and preparation method thereof
Through the mechanical blending and chemical grafting reaction of modified Duobi carbon nanotubes and LLDPE, combined with polyisobutylene, ethylene-vinyl acetate copolymer, antioxidant and silica, the PE winding film is solved by using a twin-screw extrusion process. Toughness and aging resistance problems have achieved high toughness and efficient production of winding film preparation.
Patent Information
- Application Number
- CN202411432352.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
AI Technical Summary
The existing PE wrap films are poorly tough and prone to aging in actual use, making them difficult to meet the needs of industrial and commercial applications.
By mechanically blending the modified Duobi carbon nanotubes with LLDPE, and introducing 4-aminobenzophenone through chemical grafting reaction, forming amide bonds, improving the dispersion and interaction force of the carbon nanotubes, and adding poly Isobutylene, ethylene-vinyl acetate copolymer, antioxidant and silica were used to prepare a high toughness winding film using twin screw extrusion process.
It significantly improves the toughness and aging resistance of the wound film, enhances its tensile strength and elongation at break, and simplifies the production process and improves production efficiency.
Smart Images

Figure BDA0005084002940000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging materials, and particularly relates to a high-toughness stretch film and a preparation method thereof. Background Art
[0002] Stretch film is an industrial film product that can be used for manual stretch film or machine stretch film. It can be widely used in the centralized packaging of various goods. It can wrap the goods stacked on the pallet to make the packaging more stable and tidy. It has been widely used in foreign trade export, papermaking, hardware, plastic chemicals, building materials, food and medicine industries.
[0003] The main raw materials of stretch film include PVC, EVA, PE, etc. Among them, PE stretch film has become an important development direction in the field of stretch film production due to its significant advantages, such as high production efficiency, excellent environmental adaptability, excellent product quality, reasonable price, non-toxicity and no odor. Since the late 1980s, my country has begun to develop PE stretch film, and by the early 1990s, its application has been relatively widespread. In recent years, with the continuous growth of my country's industrial product exports, the increase in the demand for forage preservation in agriculture and animal husbandry, and the popularization of the use of stretch film in households and supermarkets, the demand for stretch film has shown a trend of continuous growth, which has further promoted the rapid development of PE stretch film.
[0004] At present, the conventional PE stretch film used in the market still has problems such as poor toughness and easy aging in actual use. In summary, it is urgent to develop a high-toughness, aging-resistant PE stretch film. Summary of the invention
[0005] In order to solve the problems that the conventional PE stretch film mentioned in the background technology still has poor toughness and easy aging during actual use, the present invention provides a high-toughness stretch film and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A high-toughness stretch film comprises the following raw materials in parts by weight: 95-100 parts of modified LLDPE, 3-5 parts of adhesive, 3-5 parts of silicon dioxide, and 3-5 parts of antioxidant.
[0008] Further, the modified LLDPE is prepared by the following steps:
[0009] Weigh the modified multi-walled carbon nanotubes and LLDPE respectively, and use a mixer to heat at 60-80 rpm and 180-200° C. for 20-30 min to obtain modified LLDPE;
[0010] The mass ratio of the modified multi-walled carbon nanotubes to LLDPE is 0.15:500.
[0011] Further, the modified multi-walled carbon nanotubes are prepared by the following steps:
[0012] Step S1: Add multi-walled carbon nanotubes and mixed acid solution into a three-necked flask, stir mechanically at 30°C for 30 minutes, heat to 60°C and continue stirring for 4 hours, filter with a microporous filter membrane after the reaction is completed, wash with deionized water until the washing liquid is neutral, and vacuum dry at 70°C for 12 hours to obtain oxidized multi-walled carbon nanotubes, ultrasonically disperse the oxidized multi-walled carbon nanotubes in thionyl chloride, add DMF as a catalyst, stir and reflux for 24 hours, after the reaction is completed, remove excess thionyl chloride by vacuum distillation, wash the product with tetrahydrofuran, and vacuum dry at 70°C for 12 hours to obtain multi-walled carbon nanotubes with acyl chloride groups on the surface;
[0013] The amount ratio of multi-walled carbon nanotubes to the mixed acid solution is 2-3 g: 240 mL, the mixed acid solution is composed of 98% concentrated sulfuric acid and 65% concentrated nitric acid in a volume ratio of 180: 60, and the amount ratio of oxidized multi-walled carbon nanotubes, thionyl chloride and DMF is 1.5-2 g: 200 mL: 2 mL;
[0014] Step S2: Weigh 4-aminobenzophenone and dissolve it in DMF, then add multi-walled carbon nanotubes with acyl chloride groups on the surface, and ultrasonically disperse for 30 minutes, and stir at 40° C. to react for 24 hours. After the reaction is completed, cool to room temperature, filter with a microporous filter membrane, wash the product with DMF several times to remove physically adsorbed 4-aminobenzophenone, and vacuum dry at 120° C. for 12 hours to obtain modified multi-walled carbon nanotubes;
[0015] The amount ratio of 4-aminobenzophenone, DMF and multi-walled carbon nanotubes with acyl chloride groups on the surface is 4-6g:50mL:0.15g.
[0016] In the above reaction, when the carbon nanotubes are treated with a mixture of 98% concentrated sulfuric acid and 65% concentrated nitric acid, the 65% concentrated nitric acid uses its strong oxidizing property to carry out an oxidation reaction on the surface of the carbon nanotubes, and the 98% concentrated sulfuric acid plays an auxiliary role, absorbing the moisture generated during the reaction through its strong water absorption, keeping the reaction system dry, and promoting the reaction to proceed in the positive direction. A high density of carboxyl oxygen-containing polar groups are generated on the surface of the carbon nanotubes, and thionyl chloride reacts with the carboxyl groups on the surface of the carbon nanotubes under heating conditions to obtain multi-walled carbon nanotubes with acyl chloride groups. Then, the amino group in 4-aminobenzophenone acts as a nucleophilic reagent to attack the carbonyl carbon atom of the acyl chloride group to form an intermediate, and the intermediate subsequently loses hydrogen chloride to form an amide bond, thereby connecting 4-aminobenzophenone to the surface of the multi-walled carbon nanotube with the acyl chloride group through chemical grafting to obtain modified carbon nanotubes.
[0017] Furthermore, the adhesive is at least one of polyisobutylene and ethylene-vinyl acetate copolymer.
[0018] Furthermore, the antioxidant is at least one of antioxidant 1010 and tris(2,4-di-tert-butylphenyl)phosphite.
[0019] The method for preparing the high-toughness stretch film comprises the following steps:
[0020] The modified LLDPE, adhesive, silicon dioxide and antioxidant are accurately weighed and mixed until uniform, the uniformly mixed materials are subjected to twin-screw extrusion, cast into film, and rolled to obtain a high-toughness stretch film.
[0021] Among them, the screw diameter of the twin-screw extruder is 75mm, the aspect ratio is 30:1, the die gap is 1mm, the twin-screw extruder includes 4 temperature zones, 1 die, and 1 head. The first temperature zone is 170°C, the second temperature zone is 170°C, the third temperature zone is 200°C, the fourth temperature zone is 200°C, the die temperature is 210°C, the head temperature is 220°C, and the casting temperature is 200°C.
[0022] Beneficial effects of the present invention:
[0023] 1. The present invention mechanically blends linear low-density polyethylene and modified multi-walled carbon nanotubes to obtain modified linear low-density polyethylene. The multi-walled carbon nanotubes have the characteristics of small radial size and relatively large length and diameter, which can significantly improve the toughness of linear low-density polyethylene, thereby improving the toughness of the winding film. Further, by introducing 4-aminobenzophenone, the compound reacts chemically with the multi-walled carbon nanotubes with acyl chloride groups, forming amide bonds and introducing benzene rings. These functional groups can increase the interaction force of the carbon nanotubes' surrounding environment, and 4-aminobenzophenone has a certain volume and spatial structure. When it is connected to the surface of the carbon nanotubes through amide bonds, the steric hindrance between the carbon nanotubes will be increased, thereby improving the dispersibility of the carbon nanotubes. In addition, 4-aminobenzophenone belongs to the benzophenone class of compounds. Benzophenone compounds usually contain a benzene ring and a carbonyl structure. These functional groups can form intramolecular hydrogen bonds to form a chelate ring structure. When ultraviolet rays irradiate the benzophenone compounds, the hydrogen bonds in the molecules oscillate, and the stable chelate ring opens, converting the absorbed ultraviolet energy into heat energy or releasing it in the form of harmless low-energy radiation, thereby avoiding ultraviolet damage to the material and increasing the aging resistance of the stretch film.
[0024] 2. The present invention adopts a simplified process flow when preparing the high-toughness stretch film, thereby significantly reducing the production time and improving the production efficiency. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] The high-toughness wrapping film described in this embodiment includes the following raw materials in parts by weight: 100 parts of modified LLDPE, 5 parts of polyisobutylene and ethylene-vinyl acetate copolymer, 5 parts of silicon dioxide, 5 parts of antioxidant 1010 and tris(2,4-di-tert-butylphenyl) phosphite, wherein the amount ratio of polyisobutylene and ethylene-vinyl acetate copolymer is 1:1, and the amount ratio of antioxidant 1010 and tris(2,4-di-tert-butylphenyl) phosphite is 1:1.
[0028] The modified LLDPE is prepared by the following steps:
[0029] 0.15 g of modified multi-walled carbon nanotubes and 500 g of LLDPE were weighed separately, and heated at 200° C. for 30 min at 80 rpm to obtain modified LLDPE.
[0030] The modified multi-walled carbon nanotubes are prepared by the following steps:
[0031] Step S1: Add 3g of multi-walled carbon nanotubes, 180mL of 98% concentrated sulfuric acid and 60mL of 65% concentrated nitric acid into a three-necked flask, stir mechanically at 30°C for 30min, heat to 60°C and continue stirring for 4h, filter with a microporous filter membrane after the reaction is completed, wash with deionized water until the washing liquid is neutral, and vacuum dry at 70°C for 12h to obtain oxidized multi-walled carbon nanotubes, ultrasonically disperse 2g of oxidized multi-walled carbon nanotubes in 200mL of thionyl chloride, add 2mL of DMF as a catalyst, stir and reflux for 24h, after the reaction is completed, remove excess thionyl chloride by vacuum distillation, wash the product with tetrahydrofuran, and vacuum dry at 70°C for 12h to obtain multi-walled carbon nanotubes with acyl chloride groups on the surface;
[0032] Step S2: 6 g of 4-aminobenzophenone was weighed and dissolved in 50 mL of DMF, and then 0.15 g of multi-walled carbon nanotubes with acyl chloride groups on the surface were added. After ultrasonic dispersion for 30 min, the mixture was stirred at 40° C. for 24 h. After the reaction was completed, the mixture was cooled to room temperature and filtered with a microporous filter membrane. The product was washed with DMF several times to remove physically adsorbed 4-aminobenzophenone, and vacuum dried at 120° C. for 12 h to obtain modified multi-walled carbon nanotubes.
[0033] The method for preparing the high-toughness stretch film comprises the following steps:
[0034] Accurately weigh modified LLDPE, polyisobutylene and ethylene-vinyl acetate copolymer, silicon dioxide, antioxidant 1010 and tris(2,4-di-tert-butylphenyl)phosphite, and mix them until they are uniform, extrude the uniformly mixed materials with twin screws, cast the high-temperature extruded materials into films, and roll them to obtain high-toughness wrapping films. The screw diameter of the twin-screw extruder is 75mm, the aspect ratio is 30:1, and the die gap is 1mm. The twin-screw extruder includes 4 temperature zones, 1 die, and 1 head. The first temperature zone is 170°C, the second temperature zone is 170°C, the third temperature zone is 200°C, the fourth temperature zone is 200°C, the die temperature is 210°C, the head temperature is 220°C, and the casting temperature is 200°C.
[0035] Example 2
[0036] The high-toughness stretch film described in this embodiment includes the following raw materials in parts by weight: 98 parts of modified LLDPE, 4 parts of polyisobutylene, 4 parts of silicon dioxide, and 4 parts of antioxidant 1010.
[0037] The rest is the same as Example 1, except that, in the preparation process of modified LLDPE: the mixer is heated at 70 rpm and 190° C. for 25 min to obtain modified LLDPE; in the preparation process of modified multi-walled carbon nanotubes: the amount of multi-walled carbon nanotubes is 2.5 g, the amount of oxidized multi-walled carbon nanotubes is 1.75 g, and the amount of multi-walled carbon nanotubes with acyl chloride groups on the surface is 5 g.
[0038] Example 3
[0039] The high-toughness stretch film described in this embodiment includes the following raw materials in parts by weight: 95 parts of modified LLDPE, 3 parts of ethylene-vinyl acetate copolymer, 3 parts of silicon dioxide, and 3 parts of tris(2,4-di-tert-butylphenyl)phosphite.
[0040] The rest is the same as Example 1, except that, in the preparation process of modified LLDPE: the mixer is heated at 80 rpm and 200° C. for 30 min to obtain modified LLDPE; in the preparation process of modified multi-walled carbon nanotubes: the amount of multi-walled carbon nanotubes is 2 g, the amount of oxidized multi-walled carbon nanotubes is 1.5 g, and the amount of multi-walled carbon nanotubes with acyl chloride groups on the surface is 4 g.
[0041] Comparative Example 1
[0042] The rest is the same as Example 1, except that the modified multi-walled carbon nanotubes are replaced by multi-walled carbon nanotubes during the preparation of the modified LLDPE.
[0043] Comparative Example 2
[0044] The rest is the same as Example 1, except that LLDPE is directly used in the process of preparing the stretch film.
[0045] The following performance tests were performed on the stretch films prepared in Examples 1-3 and Comparative Examples 1 and 2, and the items are as follows:
[0046] 1. Mechanical properties: The mechanical properties of the stretch film were tested using an electronic universal testing machine to obtain the tensile strength and elongation at break. According to GB / T1040.3-2006 standard, at least five dumbbell-shaped specimens were tested and their average values were calculated. The test gauge length was 30 mm and the tensile speed was 50 mm / min. The test results are shown in Table 1.
[0047] 2. Xenon lamp artificial accelerated aging test: The test was carried out in accordance with GB / T16442.2-1999, the test temperature was 65℃±3℃, the relative humidity was (65℃±3)%, and the test results are shown in Table 2;
[0048] Table 1
[0049] project Tensile strength MPa Elongation at break % Example 1 29.5 535 Example 2 29.1 532 Example 3 28.8 529 Comparative Example 1 27.4 492 Comparative Example 2 26.1 468
[0050] It can be seen that the tensile strength and elongation at break of the wrapping films prepared in Examples 1-3 are significantly better than those of Comparative Examples 1 and 2. The wrapping film prepared by the preparation method of the present invention has the advantages of high tensile strength, good toughness and high elongation at break.
[0051] Table 2
[0052]
[0053] It can be seen from the data in Table 2 that the aging resistance of the wrapping films obtained in Examples 1-3 is better than that of the wrapping films obtained in Comparative Examples 1-3.
[0054] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0055] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high-toughness stretch film, characterized in that: The invention comprises the following raw materials in parts by weight: 95-100 parts of modified LLDPE, 3-5 parts of adhesive, 3-5 parts of silicon dioxide and 3-5 parts of antioxidant.
2. The high-toughness stretch film according to claim 1, characterized in that: Modified LLDPE is made by the following steps: The modified multi-walled carbon nanotubes and LLDPE were weighed separately, and heated at 180-200° C. for 20-30 min using a mixer at 60-80 rpm to obtain modified LLDPE.
3. The high-toughness stretch film according to claim 2, characterized in that: The mass ratio of modified multi-walled carbon nanotubes to LLDPE is 0.15:
500.
4. The high-toughness stretch film according to claim 2, characterized in that: Modified multi-walled carbon nanotubes are prepared by the following steps: Step S1: Add multi-walled carbon nanotubes and mixed acid solution into a flask, stir at 30°C for 30 minutes, continue stirring at 60°C for 4 hours, filter and wash with deionized water until the washing liquid is neutral, and vacuum dry at 70°C for 12 hours to obtain oxidized multi-walled carbon nanotubes, ultrasonically disperse the oxidized multi-walled carbon nanotubes in thionyl chloride, add DMF, stir and reflux for 24 hours, and after the reaction is completed, remove excess thionyl chloride by vacuum distillation, wash the product with tetrahydrofuran, and vacuum dry at 70°C for 12 hours to obtain multi-walled carbon nanotubes with acyl chloride groups on the surface; Step S2: Weigh 4-aminobenzophenone and dissolve it in DMF, then add multi-walled carbon nanotubes with acyl chloride groups on the surface, and ultrasonically disperse for 30 minutes, stir and react at 40°C for 24 hours. After the reaction is completed, cool to room temperature, filter the product, wash it with DMF, and vacuum dry it at 120°C for 12 hours to obtain modified multi-walled carbon nanotubes.
5. The high-toughness stretch film according to claim 4, characterized in that: The dosage ratio of multi-walled carbon nanotubes and mixed acid solution is 2-3g:240mL, the mixed acid solution is composed of 98% concentrated sulfuric acid and 65% concentrated nitric acid in a volume ratio of 180:60, and the dosage ratio of oxidized multi-walled carbon nanotubes, thionyl chloride and DMF is 1.5-2g:200mL:2mL.
6. The high-toughness stretch film according to claim 4, characterized in that: The usage ratio of 4-aminobenzophenone, DMF and multi-walled carbon nanotubes with acyl chloride groups on the surface is 4-6g:50mL:0.15g.
7. The high-toughness stretch film according to claim 1, characterized in that: The adhesive is at least one of polyisobutylene and ethylene-vinyl acetate copolymer.
8. The high-toughness stretch film according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010 and tris(2,4-di-tert-butylphenyl)phosphite.
9. The method for preparing a high-toughness stretch film according to any one of claims 1 to 8, characterized in that: The following steps are involved: The modified LLDPE, adhesive, silicon dioxide and antioxidant are accurately weighed and mixed until uniform, the uniformly mixed materials are subjected to twin-screw extrusion, cast into film, and rolled to obtain a high-toughness stretch film.
10. The method for preparing a high-toughness stretch film according to claim 9, characterized in that: The screw diameter of the twin-screw extruder is 75 mm, the aspect ratio is 30:1, and the die gap is 1 mm. The twin-screw extruder includes 4 temperature zones, 1 die, and 1 head. The first temperature zone is 170°C, the second temperature zone is 170°C, the third temperature zone is 200°C, the fourth temperature zone is 200°C, the die temperature is 210°C, the head temperature is 220°C, and the casting temperature is 200°C.